Monitoring changes in agriculture using computer-assisted cartography IV Farm structure - Beazley, Susan L. (Truro , Nova Scotia, Canada Nova Scotia Agricultural College/Rural Research Centre, 1996)
Agriculture, one of Nova Scotia's most important industries, forms the foundation of many rural communities and livelihoods. The industry is highly susceptible to change, driven by market forces and technological advances. Many changes in agriculture occur slowly and over long periods of time ; others are rapid. Within any jurisdiction, such province, there is a need to comprehend such changes to facilitate informed decisions about the future of agricultural policies and programs.
Research Paper No. 17
Keywords: Farm structure